Unveiling key impact parameters and mechanistic insights towards activated biochar performance for carbon dioxide reduction - Chen, Wen Qian (2024)
Chemically activated biochar is effective in supercapacitors and water splitting, but low conductivity hinders its application as a carbon support in carbon dioxide reduction reaction (CO2RR). Based on the observed CO2RR performance from potassium hydroxide (KOH)-activated biochar, increased microporosity was hypothesized to enhance the performance, leading to selection of potassium carbonate (K2CO3) for activation. K2CO3 activation at 600℃ increased microporosity significantly, yielding a total Faradaic efficiency of 72%, compared to 60% with KOH at 800℃. Further refinement of thermal ramping rate enriched micropore content, directly boosting FEC to 82%. Additionally, K2CO3's lower activation temperature could preserve hydroxyl groups to improve ethylene selectivity. These findings demonstrate that optimizing microporosity and surface chemistry is critical for designing activated biochar-based CO2RR electrocatalysts. Despite lower electrical conductivity of activated biochar, selecting the appropriate activating agents and conditions can make it a viable alternative to carbon black-based electrocatalysts.